How Rotating Solar Atmospheric Jets Become Kelvin–Helmholtz Unstable - Zhelyazkov, Ivan; Chandra, Ramesh; Joshi, Reetika (Frontiers in Astronomy and Space Sciences, 2019)
Recent observations support the propagation of a number of magnetohydrodynamic (MHD) modes which, under some conditions, can become unstable and the developing instability is the Kelvin–Helmholtz instability (KHI). In its non-linear stage the KHI can trigger the occurrence of wave turbulence which is considered as a candidate mechanism for coronal heating. We review the modeling of tornado-like phenomena in the solar chromosphere and corona as moving weakly twisted and spinning cylindrical flux tubes, showing that the KHI rises at the excitation of high-mode MHD waves. The instability occurs within a wavenumber range whose width depends on the MHD mode number m, the plasma density contrast between the rotating jet and its environment, and also on the twists of the internal magnetic field and the jet velocity. We have studied KHI in two twisted spinning solar polar coronal hole jets, in a twisted rotating jet emerging from a filament eruption, and in a rotating macrospicule. The theoretically calculated KHI development times of a few minutes for wavelengths comparable to the half-widths of the jets are in good agreement with the observationally determined growth times only for high order (10 ⩽ m ⩽ 65) MHD modes. Therefore, we expect that the observed KHI in these cases is due to unstable high-order MHD modes.